PENGARUH TINGKAT SUKU BUNGA, PROFESI NASABAH KREDIT, EFEKTIVITAS BADAN PENGAWAS PADA NON PERFORMING LOAN - Krisna Dewi, Made Diah; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2016)
LPD is a village-owned financial enterprises, in 2012 and 2013 the number of credit LPD customers in Denpasar increased by 405 people, but collectibility of loans classified as non-performing loans (NPLs) increased. The purpose of this study is to know the interest rate, credit customers profession, and the effectiveness of regulatory bodies affect the NPL. To answer these problems this study using 68 samples and data analysis techniques, namely multiple linear regression with first tested the classical assumption, test for normality, autocorrelation test, test multikoleniaritas, and heteroscedasticity test. Based on the results of multiple regression analysis, interest rate, credit customers profession, and the effectiveness of the regulatory body partially significant effect on the NPL in Denpasar City.
Keywords: Interest Rates, Credit Customer Profession, Effectiveness of Supervisory Board, Non-Performing Loans